Evaluation of the ceo-d index in preschool children of Municipal Children's Education Centers in Foz do Iguaçu-PR (Research, Society and Development, 2022)
School is a good place to promote health due to the student's stage of development, the number of children and adolescents enrolled. The search aimed at "Describing the oral health situation of students enrolled in municipal centers for early childhood education in the city of Foz do Iguaçu". This paper is a descriptive cross-sectional study with a quantitative approach. Data collection took place from August to October 2016. 365 5-year-old children enrolled in 34 municipal centers for early childhood education participated. The research had secondary data such as enrollment forms with information on the sociodemographic profile. Dental surgeons performed the dental clinical examination, duly calibrated (Kappa coefficient = 0.90), using the DMFT index. As a result, 54.54% (n = 199) are male, 69.04% (n = 252) are white and 26.85% (n = 98) are brown. The vast majority depend on the Unified Health System (90.68%, n = 331) and have their own house (69.59%, n = 254). In addition, 30.14% (n = 110) are beneficiaries of the Bolsa Família Program. The DMFT average was 1.51. Furthermore, 37.81% (n = 138) of children dissipation at least one alteration (cavities, extraction, or fillings), with caries (1.17) being the most present. Among the participants, 15.62% (n = 57) required treatment. It was high according to the proportions of changes and emphasized the prevalence of caries at this age. This methodology can be useful in a historical series to subsidize public policies with the best description of the peculiarities that seem to exist among that health districts.